Perancangan Perbandingan Energi Hypervisors (Studi Kasus : Vmwhere Vsphere dan Proxmox) - Sholeha Deka; Chairul Mukmin (JUPITER (Jurnal Penelitian Ilmu dan Teknologi Komputer), 2023)
Server virtualization is a virtualization technique that provides hardware that can run software like physical hardware. There are many applications in using the Virtual Machine application. The benefit of this research is knowing which Virtual Machine application has the best energy. The system research method will be carried out by following the path of the PPDIOO method which has phases starting from preparing, planning, designing, implementing, operating and optimizing. The results of this study are expected to know the level of energy use and workload incurred when running the Virtual Machine application